235k views
1 vote
3(4x+3)-2=12x+7
explain please

User Miknash
by
5.2k points

1 Answer

1 vote

Answer:0=0

Step-by-step explanation:

1. Distribute

3(4+3)−2=12+7

12+9−2=12+7

2.Subtract the numbers

12+9−2=12+7

12+7=12+7

3.Subtract 7 from both sides of the equation

12+7=12+7

12+7−7=12+7−7

4.Simplify

-Subtract the number

12+7−7=12+7−7

12=12+7−7

12=12+7−7

12=12

5.Subtract 12x from both sides of the equation

12=12

12−12=12−12

6.Simplify

-Combine like terms

12−12=12−12

0=12−12

0=12−12

This took forever TvT

User Joalcego
by
5.2k points